Electroconvulsive therapy in children and adolescents in Germany: a case series from 3 university hospitals - Karl, Sebastian; Methfessel, Isabel; Weirich, Steffen; Rothermel, Boris; Crozier, Jesse; Besse, Matthias; Reinhardt, Martin; Buchmann, Johannes; Dück, Alexander; Schulz, Jan; Zilles-Wegner, David; Häßler, Frank; et al. (The journal of ECT, 2022)
Objective: Electroconvulsive therapy (ECT) is a well-established, safe, and efficacious treatment for severe psychiatric disorders. In children and adolescents, it is used much less frequently than in adults, likely because of a lack of knowledge. Methods: We retrospectively analyzed all patients aged 12 to 17 years who completed a course of ECT at 3 psychiatric university hospitals in Germany between 2010 and 2020. Clinical Global Impression Severity (CGI-S) scores were assessed based on electronic medical records. Changes in CGI-S scores were assessed using a paired samples t test. Predictors for response and remission were assessed using binomial logistic regression. Results: We included 32 patients. The CGI-S scores improved significantly from before to after ECT treatment (6.9 vs 3.9, t = 10.0, P < 0.01). A total of 40.6% of patients responded (CGI ≤ 3) and 21.9% remitted (CGI ≤ 2). The number of ineffective medication trials in the 6 months before ECT treatment was significantly associated with response (odds ratio, 0.54; P = 0.028) and remission (odds ratio, 0.31; P = 0.048). Five patients reported subjective cognitive adverse effects, 2 patients exhibited a prolonged seizure, 1 patient reported headaches, and 1 patient experienced a mild allergic reaction after anesthesia with etomidate. A total of 65.6% of patients experienced no adverse effects at all. Conclusions: This retrospective analysis found ECT to be effective and safe in children and adolescents irrespective of their main diagnosis. The reported data point to the importance of an early use of ECT for severe psychiatric diseases in child and adolescent psychiatry.
Gesehen am 19.06.2023